Beginning spring framework 2 - Van de Velde, Thomas (Indianapolis, Ind. : Wrox ; Chichester : John Wiley [distributor], 2008)
A guide to the Spring Framework provides instructions for designing and building Java server applications.
Includes index.
Keywords: Application software -- Development; Java (Computer language).; Java (Computer program language).; Web sites -- Design